A Pragmatic Analysis of Speech Acts in Instructional Videos and Their Role in Enhancing Students’ Comprehension - Yahsya, Akhrif (AL LUGHAWIYAAT: JOURNAL OF ENGLISH LANGUAGE TEACHING, 2026)
This study examines the role of speech acts in instructional videos and their impact on students’ comprehension in an English as a Foreign Language (EFL) context. Drawing on Pragmatics and speech act theory proposed by John Searle, this research aims to identify the types of speech acts used in instructional videos, analyze their pragmatic functions, and explore how they influence students’ understanding. This study employed a descriptive qualitative design with a pragmatic discourse analysis approach. The data were collected from instructional videos and semi-structured interviews involving 30 undergraduate students at STAIN Mandailing Natal. The findings reveal that directive speech acts dominate instructional discourse, accounting for approximately 65–70% of all utterances. However, the effectiveness of these directives varies depending on their degree of explicitness. Direct instructions significantly enhance comprehension, while indirect and mitigated forms often lead to pragmatic failure. The study also identifies several instances of misunderstanding, where students interpret indirect directives as optional rather than obligatory. These findings indicate that pragmatic clarity plays a crucial role in determining the effectiveness of instructional communication. This study contributes to the fields of pragmatics and educational technology by highlighting the importance of linguistic factors in digital learning environments. It suggests that effective instructional videos should prioritize explicit and pragmatically appropriate language to support students’ comprehension and engagement. Keywords:‎ Pragmatics, Speech Acts, Instructional Videos, EFL, Comprehension